The Effect of Nutritional Status and Diet on Hipertension Disesase in Tabaringan Health Care - Murfat, Zulfitriani; Wahyuni, Arifah Ayu Tri; Bamahry R., Aryanti; Kanang, Indah Lestari Daeng (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hypertension is a disease that is defined as a persistent increase in blood pressure. According to WHO, the increase in hypertension is mainly driven by several factors the main risks are unhealthy eating and living patterns, lack of physical activity, etc. For example, the diet that is thought to be the main cause contains high energy, high carbohydrates, high fat, high cholesterol, high sugar, high salt, instant food and smoking habits. This can also cause fat accumulation which over time will result in weight gain and manifest in hypertension. To determine the effect of nutritional status and diet on the incidence of hypertension at the Tabaringan Community Health Center In this research, the case control method was used with the type of analytical observational research. Data collection techniques use primary data. The collected data was analyzed using the Chi-Square Test. Respondents were taken using techniques consecutive sampling. Respondents were 64 people consisting of 32 people each with hypertension and non-hypertension groups. The results of the study showed that there was a significant relationship between nutritional status and hypertension p=0.000, animal protein diet to hypertension p=0.000, vegetable protein diet to hypertension p=0.000, vegetables diet to hypertension p=0.000, fruits diet on hypertension p=0.000. However, there was no significant relationship between carbohydrate diet and hypertension, p=0.217. There is a significant relationship between overweight/obesity nutritional status and a diet of animal protein, vegetable protein, fruits and vegetables on the incidence of hypertension at the Tabaringan Community Health Center, Makassar City.